Crystal structure of (E)-1-fluoro-4-(2-(phenylsulfonyl)vinyl)benzene, C14H11FO2S - Liu Bin; Mao Ling-Yun (Zeitschrift für Kristallographie - New Crystal Structures)
C14H11FO2S, monoclinic, P21/c, a = 8.2908(8) Å, b = 19.3233(18) Å, c = 7.9496(7) Å, β = 91.188(2)°, V = 1,273.3(2) Å3, Z = 4, R gt(F) = 0.0473, wR ref(F 2) = 0.1266, T = 296 K.